PELAKSANAAN EXERCISE THERAPY PADA KASUS POST OPERASI ANTERIOR CRUCIATE LIGAMENT - Nurnarita Laila; Sri Alna Mutia; Jumiati Jumiati (Jurnal Real Riset, 2022)
This study aims to determine the effect of exercise therapy in reducing pain, increasing joint range of motion (LGS), eliminating swelling/oedema and increasing muscle strength in postoperative anterior cruciate ligament (ACL) cases. This research is a qualitative research with a case study design, namely to determine the effect of exercise therapy in reducing pain, increasing joint range of motion (LGS), eliminating swelling/oedema and increasing muscle strength in postoperative anterior cruciate ligament (ACL) cases. The subjects in this study were patients who complained of stiffness and pain in the knees when moved. The research subject consisted of one person. Data were obtained by conducting interviews, observation and exercise therapy in cases of postoperative anterior cruciate ligament. The results showed that after doing physiotherapy intervention by doing exercise therapy it was known that exercise therapy could reduce pain, increase the range of motion of the joints (LGS), eliminate swelling/oedema and decrease muscle strength in cases of postoperative anterior cruciate ligament. After getting therapy 6 times using exercise therapy which includes passive motion exercises, active motion, static contraction exercises, exercises using a stationary bicycle and exercises using a stationary bicycle and walking exercises using crutches. The patient has experienced changes, but not too maximal. By giving these interventions can accelerate the healing factor.Keywords: exercise therapy, postoperative, anterior cruciate ligament